2022
DOI: 10.1007/s00277-022-04862-3
|View full text |Cite
|
Sign up to set email alerts
|

Relapse surveillance of acute myeloid leukemia patients in first remission after consolidation chemotherapy: diagnostic value of regular bone marrow aspirations

Abstract: ‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬AbstractThe optimal follow-up care for relapse detection in acute myeloid leukemia (AML) patients in first remission after consolidation therapy with intensive chemotherapy is not established. In this retrospective study, we evaluate the diagnostic value of an intensive relapse surveillance strategy by regular bone marrow aspirations (BMA) in these patients. We identified 86 patients with newly diagnosed non-promyelocytic AML who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This observation could indicate that differences in outcome are related to the management of treatment-related complications and primary refractory or relapsed disease, since most relapses occur within the first 2 to 3 years after the achievement of complete remission. 35,36 Consistent with this observation, a 2017 study found that marital status and neighborhood SES are independent risk factors for 60-day mortality in patients with AML. 37 In addition, the management of common complications related to the treatment of AML, ie, neutropenic infections, where rapid antibiotic management is required, 38 could also contribute to this difference.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This observation could indicate that differences in outcome are related to the management of treatment-related complications and primary refractory or relapsed disease, since most relapses occur within the first 2 to 3 years after the achievement of complete remission. 35,36 Consistent with this observation, a 2017 study found that marital status and neighborhood SES are independent risk factors for 60-day mortality in patients with AML. 37 In addition, the management of common complications related to the treatment of AML, ie, neutropenic infections, where rapid antibiotic management is required, 38 could also contribute to this difference.…”
Section: Discussionmentioning
confidence: 79%
“…When examining the survival difference in AML, we found that most of the increased hazard for the low SES group was within 2 years after diagnosis. This observation could indicate that differences in outcome are related to the management of treatment-related complications and primary refractory or relapsed disease, since most relapses occur within the first 2 to 3 years after the achievement of complete remission . Consistent with this observation, a 2017 study found that marital status and neighborhood SES are independent risk factors for 60-day mortality in patients with AML .…”
Section: Discussionmentioning
confidence: 89%
“…Minimal residual disease (MRD) denotes the existence of malignant cells that remain in the body of a cancer patient following a particular treatment regimen, without clinical symptoms or signs of disease, and is not detectable by cellular morphology or routine screening methods. This elucidates the reasons that the majority of patients who attain a state of the complete response still relapse within years (1)(2)(3). MRD mainly applies to hematological malignancies and solid tumors (4).…”
Section: Introductionmentioning
confidence: 81%
“… 1 Notably, relapse and drug resistance are the biggest challenges facing AML therapy, with relapse rates of leukemia (including allo‐HSCT) of up to 40%–50% in all age groups. 2 , 3 New drug venetoclax shows high remission rates, but has a short‐lived effect, is resistant, and eventually leads to refractory relapses. 4 Therefore, more research and exploration are still needed to overcome the above problems.…”
Section: Introductionmentioning
confidence: 99%